2020
DOI: 10.21037/apm-20-1264
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the nursing care of intracranial carbapenem-resistant Escherichia coli infection after severe traumatic brain injury: a case report

Abstract: has become a global public health problem with widespread rapid increase. Resulting in high morbidity, disability, and mortality, CRE brings considerable challenges to clinical treatment and severe burdens to society (2,3). It is much easier for the elderly, immunocompromised and critically ill patients to infect CRE. The mortality rate is between 40% and 50% for severe patients with CRE bloodstream infections (4). In order to effectively decrease case-fatality rates among patients with the infections owing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
1
1
0
Order By: Relevance
“…By adjusting the height of the drainage bag at any time to control the drainage flow rate, it was controlled at 10-15ml per hour [9] . There was no significant difference in average drainage speed, drainage time, and total drainage flow rate.Compared with the conventional drainage mode, the fluctuation of drainage speed was small, ensuring a slow and uniform flow rate, and avoiding the formation of a large pressure gradient due to excessive drainage flow rate per unit time, Therefore, the incidence of complications was lower, which is consistent with the research results of scholars such as Zhou Xiaoxiao [10][11][12] . In addition, this article compared the cerebrospinal fluid indicators and intracranial pressure before and after drainage in two groups.…”
Section: Discussionsupporting
confidence: 81%
“…By adjusting the height of the drainage bag at any time to control the drainage flow rate, it was controlled at 10-15ml per hour [9] . There was no significant difference in average drainage speed, drainage time, and total drainage flow rate.Compared with the conventional drainage mode, the fluctuation of drainage speed was small, ensuring a slow and uniform flow rate, and avoiding the formation of a large pressure gradient due to excessive drainage flow rate per unit time, Therefore, the incidence of complications was lower, which is consistent with the research results of scholars such as Zhou Xiaoxiao [10][11][12] . In addition, this article compared the cerebrospinal fluid indicators and intracranial pressure before and after drainage in two groups.…”
Section: Discussionsupporting
confidence: 81%
“…It is reported that approximately 10 million people suffer TBI annually, which places a significant heavy load on public health (1,2). TBI negatively impacts individuals' life quality and brings a heavy family and societal burden (3). Because of the immediate and delayed effects of injury, the pathology of TBI is not merely complex, but is heterogeneous (4).…”
Section: Introductionmentioning
confidence: 99%